2020
DOI: 10.1002/ijgo.13424
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia for vaginal birth: Secondary analysis from the WHO Multicountry Survey on Maternal and Newborn Health

Abstract: Objective To evaluate the use of analgesia during labor in women who had a vaginal birth and to determine the factors associated with its use. Methods A secondary analysis was performed of the WHO Multicountry Survey on Maternal and Newborn Health, a cross‐sectional, facility‐based survey including 359 healthcare facilities in 29 countries. The prevalence of analgesia use for vaginal birth in different countries was reported according to the Human Development Index (HDI). Sociodemographic and obstetric charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…There is contradictory information about the influence of parity on the primary choice of EDA, with some stating that primiparas less often than multiparas include EDA in their labor plans [9,17], with others on the contrary indicating that primiparas choose to have EDA more often than multiparas [18]. An Australian study on a group of 2445 women indicated that women who used EDA in previous labors were more likely to have EDA, as well as those with higher education or of higher income.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory information about the influence of parity on the primary choice of EDA, with some stating that primiparas less often than multiparas include EDA in their labor plans [9,17], with others on the contrary indicating that primiparas choose to have EDA more often than multiparas [18]. An Australian study on a group of 2445 women indicated that women who used EDA in previous labors were more likely to have EDA, as well as those with higher education or of higher income.…”
Section: Discussionmentioning
confidence: 99%
“…While neuraxial analgesia provides the most effective labor pain relief, availability, contraindications, and preferences may impact its use in labor [ 7 ]. Souza et al evaluated use of labor analgesia for vaginal delivery in Africa, Asia, Middle East, and Latin America, in a cross-sectional, facility-based survey of 359 healthcare facilities in 29 countries [ 8 ]. Sociodemographic and obstetric characteristics of laboring women who did and did not receive labor analgesia were presented.…”
Section: Neuraxial Analgesiamentioning
confidence: 99%
“…The ability to choose efficacious analgesia options is an essential contribution to the labor experience. Prior to labor, women may seek information regarding labor analgesia options and may not necessarily have a fixed decision regarding the analgesia they prefer [1][2][3]. Many factors may impact the decision regarding labor analgesia, including concurrent comorbidities such as high body mass index, cardiac disease, obstetric history such as prior cesarean delivery, preeclampsia, and available monitoring options.…”
Section: Introductionmentioning
confidence: 99%
“…Epidural analgesia effectively relieves the pain during the progress of labor, but it is still not available consistently in many institutions. Though the rate of epidural analgesia using has been increased in China, nearly 57 % in some institutions recently [1], only 4 % of total women and 21.6 % of low-risk women received labor epidural analgesia in the whole world [2,3].…”
Section: Introductionmentioning
confidence: 99%